Experts’ Agreement of the Personalized m-Learning Curriculum Model Based on Fuzzy Delphi Method - MOGANADASS RAMALINGAM; SITI HAJAR HALILI; SAEDAH SIRAJ (Indonesian Research Journal in Education |IRJE|, 2019)
The purpose of this study was to identify the experts’ agreement on the suitability of the personalized m-learning curriculum model. A total of 25 experts were selected to evaluate the model. A Fuzzy Delphi Method was used to identify suitability of the elements in personalized m-learning model. Based on the overall findings, all the items have met the requirements needed in the triangular fuzzy number and meet the deffuzification process (more than the Alpha α - cut value of 0.5). This revealed that all the experts consensually agreed with all questionnaire items. Hence, the proposed personalized m-learning curriculum implementation model is suitable to serve as a guideline for the instructor in implementing personalized m-learning. The new personalized m-learning elements for another course or programme could be determined based on the experts’ opinions. This will enable the development of personalized m-learning model that could be implemented for any course or programme.